Emotional and informational social support from health visitors and breastfeeding outcomes in the UK - A Chambers; EH Emmott; S Myers; AE Page (BMC, 2023)
Abstract Background Shorter breastfeeding duration is associated with detrimental consequences for infant health/development and maternal health. Previous studies suggest social support is essential in maintaining breast/chest-feeding and helping to improve general infant feeding experiences. Public health bodies therefore work to support breastfeeding in the UK, yet UK breastfeeding rates continue to be one of the lowest globally. With this, a better understanding of the effectiveness and quality of infant feeding support is required. In the UK, health visitors (community public health nurses specialising in working with families with a child aged 0-5 years) have been positioned as one of the key providers of breast/chest-feeding support. Research evidence suggests that both inadequate informational support and poor/negative emotional support can lead to poor breastfeeding experiences and early breastfeeding cessation. Thus, this study tests the hypothesis that emotional support from health visitors moderates the relationship between informational support and breastfeeding duration/infant feeding experience among UK mothers. Methods We ran cox and binary logistic regression models on data from 565 UK mothers, collected as part of a 2017-2018 retrospective online survey on social support and infant feeding. Results Informational support, compared to emotional support, was a less important predictor of both breastfeeding duration and experience. Supportive emotional support with unhelpful or absent informational support was associated with the lowest hazard of breastfeeding cessation before 3 months. Results for breastfeeding experience followed similar trends, where positive experience was associated with supportive emotional and unhelpful informational support. Negative experiences were less consistent; however, a higher probability of negative experience was found when both types of support were reported as unsupportive. Conclusions Our findings point to the importance of health visitors providing emotional support to bolster the continuation of breastfeeding and encourage a positive subjective experience of infant feeding. The emphasis of emotional support in our results encourages increased allocation of resources and training opportunities to ensure health visitors are able to provide enhanced emotional support. Lowering health visitors caseloads to allow for personalised care is just one actionable example that may improve breastfeeding outcomes in the UK.